Description of standard Spanish in the poetry of Nicolás Guillén. First approach (Islas, 2023)
Introduction: This article presents results from the study «España, poema en cuatro angustias y una esperanza by Nicolás Guillén», part of the diploma thesis of the first author and a component of the Poetic Lexicon of Nicolás Guillén project directed by the second author, conducted at the Center for Applied Linguistics in Santiago de Cuba under the direction of the second author.Methods: Using the Textual Corpus Tagger and Processor (ETIPROCT), tags were assigned to lexical units in the poem based on their corresponding grammatical category, along with extracting significant linguo-statistical information.Results: The main findings highlight the prevalence of common nouns across all word classes, the notable use of verbal periphrases, the significance of forms belonging to conjunctions and prepositions due to their high frequency, as well as the use of some ingenious forms.Conclusions: The study revealed notable aspects of Guillén's poetic lexicon in the analyzed text, such as the use of proper and common nouns and verbal periphrases.
Keywords: Nicolás Guillén; natural language processing; sublexicon of standard Spanish; ETIPROCT; ambiguity; grammatical tagging